Maternal whole blood mRNA signatures identify women at risk of early preeclampsia: a longitudinal study. (2nd November 2021) - Tarca, Adi L.; Romero, Roberto; Erez, Offer; Gudicha, Dereje W.; Than, Nandor Gabor; Benshalom-Tirosh, Neta; Pacora, Percy; Hsu, Chaur-Dong; Chaiworapongsa, Tinnakorn; Hassan, Sonia S.; Gomez-Lopez, Nardhy
Abstract: Purpose: To determine whether previously established mRNA signatures are predictive of early preeclampsia when evaluated by maternal cellular transcriptome analysis in samples collected before clinical manifestation. Materials and methods: We profiled gene expression at exon-level resolution in whole blood samples collected longitudinally from 49 women with normal pregnancy (controls) and 13 with early preeclampsia (delivery <34 weeks of gestation). After preprocessing and removal of gestational age-related trends in gene expression, data were converted into Z-scores based on the mean and standard deviation among controls for six gestational-age intervals. The average Z-scores of mRNAs in each previously established signature considered herein were compared between cases and controls at 9–11, 11–17, 17–22, 22–28, 28–32, and 32–34 weeks of gestation. Results: ( 1) Average expression of the 16-gene untargeted cellular mRNA signature was higher in women diagnosed with early preeclampsia at 32–34 weeks of gestation, yet more importantly, also prior to diagnosis at 28–32 weeks and 22–28 weeks of gestation, compared to controls (all, p  < .05). (2) A combination of four genes from this signature, including a long non-protein coding RNA [H19 imprinted maternally expressed transcript ( H19 )], fibronectin 1 ( FN1 ), tubulin beta-6 class V ( TUBB6 ), and formyl peptide receptor 3 ( FPR3 ) had a sensitivity of 0.85 (0.55–0.98) and a specificity of 0.92 (0.8–0.98) for prediction of early preeclampsia at 22–28 weeks of gestation. (3) H19, FN1, and TUBB6 were increased in women with early preeclampsia as early as 11–17 weeks of gestation (all, p  < .05). (4) After diagnosis at 32–34 weeks, but also prior to diagnosis at 11–17 weeks, women destined to have early preeclampsia showed a coordinated increase in whole blood expression of several single-cell placental signatures, including the 20-gene signature of extravillous trophoblast (all, p  < .05). (5) A combination of three mRNAs from the extravillous trophoblast signature ( MMP11, SLC6A2, and IL18BP ) predicted early preeclampsia at 11–17 weeks of gestation with a sensitivity of 0.83 (0.52–0.98) and specificity of 0.94 (0.79–0.99). Conclusions: Circulating early transcriptomic markers for preeclampsia can be found either by untargeted profiling of the cellular transcriptome or by focusing on placental cell-specific mRNAs. The untargeted cellular mRNA signature was consistently increased in early preeclampsia after 22 weeks of gestation, and individual mRNAs of this signature were significantly increased as early as 11–17 weeks of gestation. Several single-cell placental signatures predicted future development of the disease at 11–17 weeks and were also increased in women already diagnosed at 32–34 weeks of gestation.